Do weight perception and bullying victimization account for links between weight status and mental health among adolescents? - Karen A. Patte; Maram Livermore; Wei Qian; Scott T. Leatherdale (BMC, 2021)
Abstract Background The purpose of this study was to explore whether the way youth perceive their weight and their experiences of bullying victimization account for the increased risk of depression and anxiety symptoms, and poor psychosocial well-being, associated with overweight/obesity in a large sample of Canadian secondary school students. We also explored if associations differed by gender. Methods We used cross-sectional survey data from year 7 (2018-19) of the COMPASS study. The sample included 57,059 students in grades 9-12 (Secondary III-V in Quebec) at 134 Canadian secondary schools (Alberta, British Columbia, Ontario, Quebec). First, multiple regression models tested associations between body mass index (BMI) classification and mental health outcomes (anxiety [GAD-7] and depression [CESD-10] symptoms, and psychosocial well-being [Diener's Flourishing Scale]). Second, weight perception and bullying victimization were added to the models. Models were stratified by gender and controlled for sociodemographic covariates and school clustering. Results When weight perception and bullying victimization were added to the models, obesity BMI status no longer predicted internalizing symptoms and flourishing scores relative to normal-weight BMIs. Students with 'overweight' or 'underweight' perceptions, and experiences of bullying victimization in the past month, reported higher anxiety and depressive symptomatology, and lower flourishing levels, in comparison to students with 'about right' weight perceptions and without experiences of bullying victimization, respectively, controlling for BMI status. Results were largely consistent across boys and girls. Conclusions Results suggest perceptions of weight and experiences of bullying independently contribute to differences in mental health outcomes by weight status among youth. Continued efforts targeting weight-based bullying and weight bias, and the promotion of body size acceptance and positive body image, may help reduce the risk of mental illness and poor mental health among adolescents.